Cormic Index Profile of Children with Sickle Cell Anaemia in Lagos, Nigeria - Samuel Olufemi Akodu; Olisamedua Fidelis Njokanma; Omolara Adeolu Kehinde (Anemia)
Background. Sickle cell disorders are known to have a negative effect on linear growth. This could potentially affect proportional growth and, hence, Cormic Index. Objective. To determine the Cormic Index in the sickle cell anaemia population in Lagos. Methodology. A consecutive sample of 100 children with haemoglobin genotype SS, aged eight months to 15 years, and 100 age and sex matched controls (haemoglobin genotype AA) was studied. Sitting height (upper segment) and full length or height were measured. Sitting height was then expressed as a percentage of full length/height (Cormic Index). Results. The mean Cormic Index decreased with age among primary subjects (SS) and AA controls. The overall mean Cormic Index among primary subjects was comparable to that of controls (55.0±4.6% versus 54.5±5.2%; 54.8±4.5% versus 53.6±4.9%) in boys and girls, respectively. In comparison with AA controls, female children with sickle cell anaemia who were older than 10 years had a significantly lower mean Cormic Index. Conclusion. There was a significant negative relationship between Cormic Index and height in subjects and controls irrespective of gender. Similarly, a significant negative correlation existed between age, sitting height, subischial leg length, weight, and Cormic Index in both subjects and controls.